Analisis Kebijakan dan Implementasi Peraturan Menteri Kesehatan Nomor 16 Tahun 2019 pada Program Jaminan Kesehatan Nasional - Dina Anjayani (BPJS Kesehatan, 2021)
The Minister of Health Regulation (PMK) Number 16 of 2019 concerning Fraud Prevention in the National Health Insurance Program (JKN) as a substitute for Minister of Health Regulation Number 36 of 2015 is still being evaluated and studied in its implementation. According to the mandate of PMK Number 16 of 2019, there is still the possibility of fraud in the implementation of JKN that has not been demonstrated and followed up on by the Fraud Prevention Team (TPF). Analyze PMK policy Number 16 of 2019 and investigate for other policy options so that their implementation works properly. The Bardach Criteria are used in the study to weight the alternative policy options that will be recommended next. The analysis result indicated that PMK Number 16 of 2019 is still stagnant, and optimizing the JKN TPF function is more feasible at this time, particularly that the PMK revision will require more time and be more complicated.